Analysis of Efforts to Improve the Performance of the Public Relation Division in The National Narcotics Board Bali - Nastiti Rahayu (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study seeks to determine how the Public Relations Division of The National Narcotics Board (Badan Narkotika Nasional, abbreviated BNN) Bali can improve its performance. In-depth interviews, observation, and documentation are employed as data collection methods. The results of the analysis demonstrate the positive effects of training and development on BNN employees, namely their enhanced ability to work in terms of precision, speed, quality of work results, and discipline. Improving work discipline, which entails imparting knowledge of work discipline to employees during training, so that they develop a work-disciplined attitude following the training. Similarly, the organization will naturally benefit from having competent employees. In this program, all information will be provided to employees; consequently, the knowledge acquired by employees will be superior and flawless, and the performance of employees in the public relations division of BNN will improve significantly.